The role of speech style between teacher and student in learning English - Mohammad Amiruddin; Ukhti Raudhatul Jannah (Intelektual Pustaka Media Utama, 2022)
This study examined the role of speech style between teachers and students in learning English. This study was ex post facto research, using quantitative approach. The students at English Department of Madura University, Indonesia were the population in this research. A sample was decided using proportional stratified random sampling technique. The data were analyzed by simple regression technique. The result of the study showed that the role of speech style between the teachers and the students in learning English is 0.62 (62%). The speech styles of the teachers and students work on students’ proficiency level in English. Conducive classroom in language learning is the requirement of the right speech styles of the teachers and the students. It makes necessary for the teachers to provide students with suitable speech style with the contexts in order to put up the classroom serving the students with substantial input.